Study of B Meson Production in p+Pb Collisions at √[S(NN)]=5.02 TeV Using Exclusive Hadronic Decays - Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Asilar, E; Bergauer, T; Brandstetter, J; Brondolin, E; Dragicevic, M; Erö, J; Flechl, M; Friedl, M; et al. (Physical review letters, 2016)
The production cross sections of the B^{+}, B^{0}, and B_{s}^{0} mesons, and of their charge conjugates, are measured via exclusive hadronic decays in p+Pb collisions at the center-of-mass energy sqrt[s_{NN}]=5.02 TeV with the CMS detector at the CERN LHC. The data set used for this analysis corresponds to an integrated luminosity of 34.6 nb^{-1}. The production cross sections are measured in the transverse momentum range between 10 and 60 GeV/c. No significant modification is observed compared to proton-proton perturbative QCD calculations scaled by the number of incoherent nucleon-nucleon collisions. These results provide a baseline for the study of in-medium b quark energy loss in Pb+Pb collisions.